Pensamento proporcional: uma metanálise qualitativa de dissertações - Miranda, Marcia Regiane (2009)
The goal of this work is to make a synthesis of investigations focused on the mathematical expressions generated (or reflected) from manifestation and development of the proportional thinking. Our study object are activities set out in thesis produced in the State of São Paulo aimed at improving the teaching and learning proportional thinking aspects. Our research methodology is characterized as a documentary denominated qualitative metanalysis study which seeks to make a systematic review of a set of surveys that produce new results or synthesis. In order to transcend the results obtained by investigations, we used in analysis, elements which we believe are essentials of theoretical, historical and curricular references. We conduct our studies based on procedures of content analysis of Bardin (2008), in a qualitative approach, leading our research according to the following phases: 1) The preparation of the documentary corpus and register selection models. 2) The first analysis of documents. 3) Second analysis. 4) The final synthesis. As a result, we verified that the activities proposed in two dissertations of the State of São Paulo have fostered expression and the development of our students proportional thinking, and privileged aspects were those that had intended to represent proportional situations through charts, tables, symbols, drawings or diagrams; using central ideas associated with directions from rational numbers, or relations and operations between them, besides their representations, to solve problems involving functions or ideas associated with the functions and their representations and using multiplication and division to solve problems involving ratio or proportional ideas